Stable W and Mo isotopic evidence for increasing redox-potentials from the Paleoarchean towards the Paleoproterozoic deep ocean. (15th September 2021) - Roué, Lucile; Kurzweil, Florian; Wille, Martin; Wegwerth, Antje; Dellwig, Olaf; Münker, Carsten; Schoenberg, Ronny
Highlights: Stable W isotope variations of Archean shales. Stable W isotopes trace redox of anoxic ferruginous, but not euxinic sediments. Eh evolution of the Archean Ocean. Abstract: The scavenging of dissolved trace metals such as chromium (Cr), molybdenum (Mo) and tungsten (W) and their authigenic enrichment in sedimentary archives mainly occur by particle shuttling that cause resolvable isotope fractionation. Because their scavenging is also dependent on the local marine redox potential and the overall marine chemical environment, the stable isotope composition of these elements in Archean sediments is widely used as paleoredox proxy. Tungsten, a new element in this tool box, is dissolved as the oxyanion tungstate (WO4 2− ) at extremely low marine redox potentials and can thus help to reconstruct the earliest changes in the marine redox state. We tested the applicability of stable W isotopes as a new paleoredox proxy of the atmosphere–ocean system. We analyzed the δ 186/184 W of Precambrian igneous rocks to investigate the detrital background δ 186/184 W signature. This Precambrian igneous inventory (PII) shows δ 186/184 W values between −0.007 and +0.097‰, identical to the range of modern igneous crustal rocks, which indicates that the average Earth's crust δ 186/184 W remained constant over billions of years. Furthermore, we present δ 186/184 W values of euxinic sediments from the Black Sea as a modern sedimentary analog, which we then compare with δ 186/184 W data of Archean and Proterozoic black shales (3.47–2.3 Ga). Modern Black Sea sapropels reveal crustal-like δ 186/184 W values between +0.050 and +0.071‰ suggesting limited authigenic enrichment of W in euxinic environments. Similarly, post-Great Oxidation Event shales (2.3 Ga) show crustal- or PII-like δ 186/184 W values indicating the deposition in euxinic or oxic environment. However, the Archean shale sample suites show elevated W concentrations and fractionated δ 186/184 W values up to +0.246‰, which we attribute to authigenic enrichment of heavy seawater W in a ferruginous setting. Thus, black shales δ 186/184 W values can help to distinguish between anoxic-ferruginous and euxinic depositional environments. Furthermore, we combine previously published Cr and Mo isotope data with new Cr and W isotope data to quantify the evolution of the marine redox state during the Archean. By combining the Eh-pH stability fields of W and Mo with the δ 186/184 W and δ 98/95 Mo values of Precambrian sediments, we suggest a 3-step evolution of the Precambrian ocean. (1) From 3.47 to 3.0 Ga, the Eh of a dominantly ferruginous ocean was between −0.4 V and −0.25 V, enabling the persistence of soluble WO4 2− but not MoO4 2− and thus only the authigenic enrichment of isotopically fractionated W. (2) Starting from 3.0 Ga, the Eh of some shallow-marine environments increased above −0.25 V, as indicated by δ 98/95 Mo values above the detrital background in shallow-marine sediments, while the Eh of the deep ocean still remained below −0.25 V indicated by the lack of authigenic Mo enrichment and fractionated δ 98/95 Mo values in deep-sea shales. (3) After 2.7 Ga elevated δ 98/95 Mo and δ 186/184 W values in deep-marine sediments suggest that the Eh of the ferruginous open-ocean now also increased above −0.25 V. We therefore suggest that the combination of δ 98/95 Mo and δ 186/184 W values of shales is a very promising tool to investigate earliest changes in marine redox conditions during the Archean.